Baby Gym Practice to Improve Motor Development among Babies in the Banjar Batannyuh at Ages 6 to 9 Months - Ni Nyoman Diah Prameswari; Indah Pramita; Antonius Tri Wahyudi (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
Every child must accomplish the child development and growth process; else, future growth and development will be delayed. Delays in children are caused by a lack of stimulation, thus stimulation may be provided in the form of baby gym to improve children's growth and development. This research aims to determine whether giving a baby gym may improve motor development in babies aged 6 to 9 months in the Banjar Batannyuh area. This study used a pre-experimental one-group pre and post-test method. This study's sample consisted of 7 babies aged 6-9 months who fulfilled the inclusion and exclusion criteria. Measurement of motor development employing KPSP. The recommended activity, baby gym, is performed three times each week for four weeks. The average pre-test score before exercise was 7.71, while the average after exercise was 9.14 after testing using paired sample t-test. With a p-value of 0.001, the increase obtained after training was 18.5%. The study's findings suggest that giving a baby gym to babies between the ages of 6 and 9 months living in Banjar Batannyuh area can improve their motor development.